Deconstructing food losses across the value chain - Delgado, Luciana; Schuster, Monica; Torero, Máximo (International Food Policy Research Institute, 2021)
The importance of reducing food loss and food waste has captured the public imagination since it became one of the targets of the United Nations Sustainable Development Goals. The urgency of this issue and the awareness of its significance to the development community has been growing steadily. Even so, policies to address food insecurity or the increasing pressure on the world’s available land that is being caused by growing populations and changing diets have aimed mainly at increasing agricultural yields and productivity. These efforts are often cost- and time-intensive and do not consider food loss and waste reduction as a tool to help meet growing food demand; nor do they consider food loss reduction as a means to ease pressure on land. Food loss also entails unnecessary greenhouse gas emissions and excessive use of scarce resources including land (FAO 2019); thus, policies to reduce food loss will also benefit the environment. Finally, cutting food loss can help disadvantaged segments of the population, as the loss of marketable food can reduce producers’ incomes and increase consumers’ expenses. Most of the literature uses the terms postharvest losses (PHL), food loss (FL), food waste (FW), and food loss and waste (FLW) interchangeably, but they rarely refer consistently to the same concept. Recent publications (FAO 2014, 2019; HLPE 2014; Lipinski et al. 2013) have tried to clarify this by defining FL as unintentional reductions in food quantity or quality before consumption, that is, from the producer to the wholesale market, inclusive. These losses usually occur in the earlier stages of the food value chain—between production and distribution. This definition, however, does not include crops that are lost before harvesting or are left in the field; nor does it include crops that are lost due to poor harvesting techniques or sharp price drops; nor crops that are not produced because of a lack of adequate agricultural inputs, such as fertilizer, or because of a shortage of available labor. In 2019, the FAO developed the Food Loss Index (FLI), following the definition of food loss mentioned above. According to the FLI, an estimated 14 percent of food produced is lost every year. The major losses are in Central Asia and Southern Asia (20.7 percent), as compared to sub-Saharan Africa, which experiences a 14 percent food loss (FAO 2019), and Latin American and the Caribbean where 11.6 percent is lost. When examining losses in terms of food groups, the highest level of loss is reported in roots, tubers, and oil-bearing crops, followed by fruits and vegetables. It is not surprising that fruits and vegetables incur high levels of loss (more than 20 percent) given their highly perishable nature.